Analisa Tata Kelola Teknologi Informasi Dan Manajemen Data Terhadap Implementasi Ai Menggunakan Cobit 2019 (Studi Kasus Pt Xyz) - Visoka, Adib Muhammad; Nadlifatin, Reny (Syntax Literate, 2025)
PT XYZ is a company engaged in providing internet services and telecommunication networks. In managing its network services and infrastructure, PT XYZ operates an Integrated Operation Center that monitors all production tools continuously on a 24/7 basis. As part of its development, PT XYZ is leveraging Artificial Intelligence (AI) to accelerate business processes and to ensure more efficient information management. To achieve these goals, effective governance of data and information management is essential. This study uses COBIT 2019, a proven and widely recognized governance framework, to identify and analyze the necessary governance requirements at PT XYZ. COBIT 2019 includes a capability level assessment mechanism based on the Capability Maturity Model Integration (CMMI), which enables the evaluation of existing management practices. Using the design factors method, seven objectives from COBIT 2019 were selected such as EDM03 (Ensured Risk Optimization), APO12 (Managed Risk), APO13 (Managed Security), BAI10 (Managed Configuration), DSS04 (Managed Continuity), DSS05 (Managed Security Services), and MEA03 (Managed Compliance with External Requirements). The results of this study include improvement steps and governance recommendations for each selected objective to reach the target state expected by stakeholders. The current assessment shows that all selected objectives are at capability level 2 (Managed), while the desired target is level 5 (Optimizing). Therefore, improvement measures based on the proposed recommendations and best practices are required. In line with COBIT 2019 framework recommendations, in order to successfully implement AI within existing business processes, PT XYZ must prioritize risk management, data and IT infrastructure security, as well as compliance with rules/regulations, so that the AI adoption is aligned with the plan, safe, effective, and efficient